Implications of bipphysical site characteristics on growth and sustainable cassava production in the savannas of Nigeria - Ekanayake, I.J.; Githunguri, C.M. (2000)
In the Nigeria savanna (derived, Guinea and Sudan) belt, continuous production of crops with short or no fallow cycle, with small amounts or no fertilizer and mixed cropping is a prevalent land use system. Cultivation of cassava as a staple supplementary food source in relatively degraded savanna lands it common. Productivity of the on-farm crop is greatly lower than its potential. Therefore we studied the effect of several biophysical factors on growth and productivity of cassava. Field data (crop, weather and soil) were obtained from three sites: Ibadan, Mokwa and Minjibir in south north transect in Nigeria. Ibadan and Mokwa are wetier, more humid, and cooler than Minjibir. Minjibir (Sudan savanna) has the highest solar radiation and water deficit. Ibadan (derived savanna) soils had highest moisture content, organic C, total N, Ca and Mg contents, and cation exchange capacity. Mokwa and Minjibir had higher soil P than Ibadan. Minjibir had the lowest K content. Mokwa (Guinea savanna) had the least compacted soil. Plant growth parameters measured at the various zones were compared. Leaf area index and production rate, weight of stems, rootstock, height, crop growth and relative growth rates of cassava plants were lowest at Minjibir. Water use efficiency of plants at Ibadan declined while it increased at Mokwa. The highest crop establishment was observed at Ibadan. Cassava plants at Mokwa had the highest number of tuberous roots, yield, harvest index, and bulking rate. This site characterization also showed the importance and pitfalls of experimental sites-analysis, scaling and use of generalized information based on the literature.